Nitrogen and sulphur co-doped crumbled graphene for the oxygen reduction reaction with improved activity and stability in acidic medium - Bhange, Siddheshwar N.; Unni, SreeKuttan M.; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2016)
Non-precious dioxygen reduction electrocatalysts have attracted great attention nowadays for the development of stable, cost-effective proton exchange membrane fuel cells. In line with the development of non-precious electrocatalysts, here we report the synthesis of a platinum-free oxygen reduction electrocatalyst based on nitrogen and sulphur co-doped crumbled graphene with trace amounts of iron. The co-doped crumbled graphene structure was obtained by simple oxidative polymerisation of ethylenedioxythiophene in aqueous solution followed by an annealing process under an inert atmosphere. This new electrocatalyst displays improved oxygen reduction activity and electrochemical stability under acidic conditions. The half-cell reaction of the 1000 degrees C annealed polyethylenedioxythiophene (PF-1000) displays only 0.1 V overpotential in both the onset and half-wave potentials compared to state-of-the-art Pt/C in an acidic environment for the ORR. More importantly, the limiting current of PF-1000 clearly surpasses the limiting current displayed by Pt/C, indicating that the crumbled assembly of the graphene flakes helps the system to expose the active sites and the porous network of the material matrix ensures extended accessibility of active sites to the electrolyte and reagent. The dioxygen reduction kinetics of PF-1000 appear similar to those of Pt/C and the system accomplishes the reduction of the dioxygen molecule through the recommended four-electron reduction pathway. The improved activity and electrochemical stability of PF-1000 are mainly attributed to the enriched and well accessible active reaction centres such as graphitic nitrogen, sulphur, and iron coordination and the peculiar morphology of PF-1000. Further, a single cell evaluation of a membrane electrode assembly based on PF-1000 as the cathode catalyst delivered a maximum power density of 193 mW cm(-2) at a cell temperature of 60 degrees C using Nafion as the proton conducting membrane.